Search for the TTH Production in Multi-Leptonic Final States with the Atlas Detector at LHC - Lasagni Manghi, Federico <1988> (Alma Mater Studiorum - Università di Bologna, 2016)
Since the discovery of the Higgs boson in 2012, the aim of the correlated physics analyses moved towards the measurement of its properties to verify the consistence with the Standard Model and to study possible signals of physics Beyond Standard Model. In particular, any discrepancy in the Higgs-SM couplings would point to new physics contributions. The ttH channels is a privileged channel for this pourpose, because it depends on a small number of BSM parameters. In this thesis the analysis of the production of a Higgs boson in association with a top and anti-top quark couple and decay into multi-leptonic final states in ATLAS at LHC is described. The analysis is focused on the channel defined by two light leptons of the same sign and no hadronic tau leptons in both Run I and Run II. The analysis is an essential preparatory step for the 2016 data-taking. After introducing the Higgs boson, LHC and the ATLAS experiment, the results of the Run I analysis are presented, which pose a first limit on the deviation of the cross section from the SM. A large part of the thesis is dedicated to the data-driven estimation of the main background of this channel, fake leptons produced in meson decays, using a technique denominated matrix method. This alternative background estimation is explained and applied to the analysis, producing alternative results. In the last part of the thesis, the first stages of the analysis of the 2015 data is shown, in preparation of the 2016 data-taking.